Testing the Functional Profiles of School Refusal Behavior and Clarifying Their Relationship With School Anxiety - Gonzálvez, Carolina; Díaz-Herrero, Ángela; Sanmartín, Ricardo; Vicent, María; Fernández-Sogorb, Aitana; García-Fernández, José M. (Frontiers in Public Health, 2020)
Students with school attendance problems are a diverse and heterogeneous group whose patterns of symptomatology can change over time. This study aims to identify different school refusal behavior profiles and to determine whether these profiles differ from each other based on four situational factors and three response systems of school anxiety across gender. The participants were 1,685 Spanish students (49% female) aged 15–18 years (M = 16.28; SD =0.97). The School Refusal Assessment Scale-Revised (SRAS-R) and the School Anxiety Inventory (SAI) were administered. Latent profile analysis revealed five school refusal behavior profiles: Non-School Refusal Behavior, Mixed School Refusal Behavior, School Refusal Behavior by Positive Reinforcement, Low School Refusal Behavior, and High School Refusal Behavior. The results indicated that High School Refusal Behavior and Mixed School Refusal Behavior groups were the most maladaptive profiles since it obtained the highest mean scores on school anxiety. In contrast, Non-School Refusal and School Refusal Behavior by Positive Reinforcement groups revealed the lowest scores in school anxiety. Non-significant gender-based differences were found, only girls were more represented in the mixed school refusal behavior profile in comparison with boys but with a small effect size. Findings are discussed in relation to the importance of promoting good mental health to prevent school attendance problems in adolescents and younger ages.